The influence of forest variation and possible effects of poaching on duiker abundance at Ngogo, Kibale National Park, Uganda - Lwanga, Jeremiah S. (African Journal of Ecology, 2006)
Duikers were censused at the Ngogo study area, Kibale National Park, Uganda, between July 2002 and August 2004. Censuses were conducted along three transects, of which, two (colonizing forests 1 and 2) were located in colonizing forests naturally replacing anthropogenic grasslands and one in old growth forest. Colonizing forest 1 was more prone to poaching than both colonizing forest 2 and the old growth forest that were closest to the research camp. Duikers that were actually sighted were identified to species, red or blue. However, on some occasions, duikers were detected by alarm calls and/or movements as they fled; these were simply recorded as duikers. Duiker abundance, regardless of species or mode of detection, was higher in colonizing forest 2 than colonizing forest 1 and the old growth forest. However, when the analysis was restricted only to duikers that were sighted, and hence identified to species, red duiker abundance was highest in colonizing forest 2 followed by the old growth forest and was lowest in colonizing forest 1; all these differences were significant. Blue duiker abundance was lowest in the old growth forest despite its proximity to the research camp; however, this was only significantly lower than in colonizing forest 2. Apart from colonizing forest 1, red duikers were significantly more abundant than blue duikers in the other two forest sections. This study suggests that forests colonizing anthropogenic grasslands may support more duikers than old growth forests; poaching in colonizing forest 1 has a severe impact on the duiker population and, red duikers are affected more severely by poaching than blue duikers.
Keywords: Bushmeat, Duikers, Old growth, Rainforest, Secondary